PENGARUH KEMAMPUAN LITERASI DIGITAL DAN TINGKAT RELIGIUSITAS SISWA TERHADAP HASIL BELAJAR AKUNTANSI DI SMK BINTANG NUSANTARA SCHOOL - Dakun, Dakun (LPPM Universitas Bina Bangsa, 2022)
Generation Z or known as the millennial generation can access, understand, evaluate, and communicate information using digital technology. With the increasing dependence of generation Z on technology in their personal life, digital literacy is an important skill that must be possessed by students to improve their learning outcomes. Generation Z tends to view the relationship between religion and religious practices in a relaxed manner compared to the following generations. This study wanted to examine the effect of digital literacy skills and students' level of religiosity on student learning outcomes. This research is quantitative research and data collection is done by direct observation, interviews, questionnaires, and tests. The results of this study indicate that digital literacy skills play an important role in influencing student learning outcomes and the level of student religiosity can motivate students to study harder it has an impact on student learning outcomes